Transferrin‐immune complex disease: A potentially overlooked gammopathy mediated by IgM and IgG. Issue 12 (15th October 2013) - Forni, Gian Luca; Pinto, Valeria; Musso, Marco; Mori, Marco; Girelli, Domenico; Caldarelli, Ilaria; Borriello, Adriana; Ragione, Fulvio Della
Abstract : The combination of marked hypersideremia, hypertransferrinemia, and monoclonal gammopathy of underdetermined significance (MGUS) should alert clinicians to the possible presence of an anti‐transferrin immunoglobulin, an uncommon acquired disorder also defined as transferrin‐immune complex disease (TICD). The authors have previously described a case of TICD with 100% transferrin saturation and liver iron overload. However, the findings in the few cases so far reported are heterogeneous, and the presence of high transferrin saturation and liver iron overload is not universal. In this article, the authors have described the identification of two additional patients with anti‐transferrin monoclonal gammopathy, hypersideremia, and hypertransferrinemia, but with incomplete transferrin saturation and no hepatic iron overload. The autoantibodies were purified by using transferrin as affinity bait and characterized. One subject showed a high‐titer monoclonal anti‐transferrin IgM with a κ‐type light chain. This finding is the first observation of IgM autoantibodies against transferrin. The other patient developed the disease after pregnancy. In this study, monoclonal antibody was an IgG mounting a κ‐type light chain with altered molecular weight. These results highlight that transferrin might induce the development of a monoclonal immune response of different classes and specificity. The identification, in a single hematologic center, of three different subjects with anti‐transferrin monoclonal gammopathy suggests that the disease probably represents a still underdiagnosed condition. From a clinical standpoint, these patients must be followed up both as MGUS and as hemochromatosis. Am. J. Hematol. 88:1045–1049, 2013. © 2013 Wiley Periodicals, Inc.